Modeling agent-based collaborative process - Ahmed M.; Ahmad M.S.; Yusoff M.Z.M. (2023)
In this paper, we develop a model for a collaborative process using software agents to resolve issues and problems with the process. The structure, workflow, and entities of the process are analyzed to develop a model in which software agents take over the communicating tasks and motivating their human counterparts by reminding, alerting, and evaluating them to comply with scheduled deadlines. The model is used as a blueprint to develop a multi-agent system for the collaborative process. 2010 Springer-Verlag Berlin Heidelberg.